A minimalist approach to stereoselective glycosylation with unprotected donors. Issue 1 (December 2017) - Le Mai Hoang, Kim; He, Jing-xi; Báti, Gábor; Chan-Park, Mary; Liu, Xue-Wei
Abstract Mechanistic study of carbohydrate interactions in biological systems calls for the chemical synthesis of these complex structures. Owing to the specific stereo-configuration at each anomeric linkage and diversity in branching, significant breakthroughs in recent years have focused on either stereoselective glycosylation methods or facile assembly of glycan chains. Here, we introduce the unification approach that offers both stereoselective glycosidic bond formation and removal of protection/deprotection steps required for further elongation. Using dialkylboryl triflate as an in situ masking reagent, a wide array of glycosyl donors carrying one to three unprotected hydroxyl groups reacts with various glycosyl acceptors to furnish the desired products with good control over regioselectivity and stereoselectivity. This approach demonstrates the feasibility of straightforward access to important structural scaffolds for complex glycoconjugate synthesis. Oligosaccharide synthesis is encumbered by multiple protection and deprotection steps. Here, the authors report a protection-free yet stereoselective and regioselective glycosylation strategy using boron-masked glycosyl donors, and demonstrate efficient synthesis of oligosaccharides over a wide substrate scope.